An Uncommon and a Rare Presentation of Acute Appendicitis with Calculus Cholecystitis in a 12-Year-Old Girl: A Case Report - Hajrah Hilal Ahmed; Muhammad Jamaluddin; Wajeeha Khalid (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Acute appendicitis is very common general surgical emergency in teenagers  while  cholecystitis  is  common in middle-aged females but cholecystitis at the age of twelve year is very rare and along with   acute appendicitis is even rarer. We describe a  case  of  12-year-old  female  who  came  to  the  outpa- tient department of Abbasi Shaheed Hospital with the  complain  of  on  and  off  pain  in  the  right  iliac fossa for the last one year. Abdominal examination was positive for  rebound  tenderness  in  right  iliac fossa at the McBurney's point.  Computed  Tomography  scan  of  whole  abdomen  showed  gallstones  with normal looking appendix. Impression of acute calculus cholecystitis  with  recurrent  acute  appen- dicitis was made.  Laparoscopy  along  with  laparoscopic  cholecystectomy  was  planned.  On  Laparoscopy appendix was found to be inflamed so laparoscopic  cholecystectomy  along  with  laparoscopic appendectomy was done via the same  ports.  Acute  appendicitis  along  with  cholecystitis due to cholelithiasis is very uncommon and very few cases have been reported in literature.